A Driving Force Analysis and Forecast for Gas Consumption Demand in China - Qing Zhu (Mathematical Problems in Engineering, 2014)
In recent years, gas has begun to be widely used in power generation as well as in manufacturing because of the environmental advantages, lower cost, and the relative safety and reliability. Accurate prediction of future gas consumption is of great importance for energy security. In this paper, we first use path analysis to select the core factors that impact gas consumption, then use the RBF-QRNN model and BVAR model separately to predict future gas consumption, and finally discuss and compare the results from the two models. The results show that if there is a positive growth in GDP, urbanization, and population, then gas consumption is expected to increase over a comparatively long time. In detail, gas consumption is expected to remain at about 25% of all energy consumption, GDP’s contribution to gas consumption is expected to be about 53%, and the urbanization rate contribution would be about 15%. Gas consumption in China is predicted to reach around 178649.23 million cubic meters by the end of 2015 and about 264698.86 million cubic meters by 2020.